Dynamics of Cultural Change: The Human Development Perspective. - ABDOLLAHIAN, MARK A.; COAN, TRAVIS G.; OH, HANA; YESILADA, BIROL A. (International Studies Quarterly, 2012)
The relationship between economic development, cultural change, and political liberalization is often explored through the lens of classic modernization theory. Recent scholarship attempts to extend classic theory to be more closely aligned with empirical reality. Under the human development perspective, economic prosperity acts as a catalyst for cultural development, leading to social values that favor liberalization, and thus promotes effective democracy. Using a systems dynamic approach, we formalize the dynamic causal structure specified in the human development perspective, develop a novel econometric procedure (Genetic Algorithm Nonlinear Least Squares) to estimate the parameters of highly nonlinear, continuous time models, and verify our formal model using five waves of data from the World Values Survey. Our results indicate that development is strongly nonlinear and path dependent: Economic progress is a necessary condition for successful secularization and expressive political behavior, which are antecedents for lasting democratic institutions. Thus, policies and institutional arrangements must be tailored to, not outpace, a nation's level of economic progress to create demand for a secular and expressive political marketplace where democratic institutions can sustain and thrive.